(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Architecture and design have always played a significant role in the tourism system, where they become key factors in hotel positioning and influence its business performance. Modern tourism demand is looking for more than the location and basic services that the hotel provides; the emphasis is on style, personalized and innovative approach. Innovations affect the specifics of design, and the overall atmosphere of the space, which architecture and design have a direct impact on. The purpose of the paper is to investigate the process of architecture and design in the context of contemporary challenges, approaches to sustainability and emotional aspects for the competitiveness of hotels on the Croatian coast. The research methodology includes qualitative processing of data collected through in-depth interviews with architects and designers of the hotel space and environment, as well as comparative analysis. The results of the research confirmed the key role of architecture and design in creating special experiences for guests and the importance of creating a pleasant atmosphere and providing superior service for success in the hotel industry. The results present a platform to the formation of a new model of competitiveness that contributes to the scientific and professional development of the hotel industry.